Real-time driver activity detection using advanced deep learning models - Md. AL Emran; Md. Ariful Islam; Md. Obaydullahn Khan; Md. Jewel Rana; Saida Tasnim Adrita; Md. Ashik Ahmed; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cognitive Neurodynamics, 2026)

Smart Innovations and Sustainability in EU Waste Material Trading: Evidence of Quantile Decomposition in EU Circular Economy Transitions - Eszter Lukács; Peter Németh; Md. Rashed; Mohammad Fakhrul Islam (Circular Economy and Sustainability, 2026)
Europe stands at the threshold of a transformative circular economy transition across the European Union (EU). However, to achieve a sustainable framework that improves resource use, transforms waste generator behavior, and guides high-polluting industries toward circular practices, the EU needs more efficient recovery networks and material circulation across member states. Using 14 years of cross-border waste recovery data from 2010 to 2023 across 27 EU countries, this study investigates the heterogeneous associations of several determinants of exports of notified waste for recovery (EWR) through the method of moments quantile regression (MMQR) to decompose location (median) and scale (dispersion) effects, alongside bootstrap quantile regression (BSQR) for robustness, the generalized method of moments (GMM) for persistence and endogeneity, and Granger causality tests for directional relationships. Our investigation identifies several policy factors associated with transboundary recovery participation and circular economy transition. The relationship also shows reverse Granger causality. AI innovation shows no significant associations with waste trade or the possibility of deployment gaps, but R&D intensity shows robust positive associations across all quantiles, with forward Granger causality supporting causal precedence. The recycling rate of municipal waste (RMW) has monotonically increasing associations in all quantiles and has bidirectional Granger causality, implying possible feedback mechanisms. These findings, put together, inform policymakers to consider market mechanisms, institutionalizing R&D investment, emphasizing infrastructure development, driving economic growth, and leveraging technological capabilities to support sustainable transboundary waste recovery networks and circular transition across the EU.

Evaluating the hepatotoxicity and nephrotoxicity of herbal medicine on swiss albino mice: an in-vivo, in-vitro and in-silico insights - Md. Murshid Alom; Md. Rausan Zamir; Nazmul Islam; Md. Khalekuzzaman; Rashed Zaman; Md. Asadul Islam (In Silico Pharmacology, 2026)

Tropical climate drivers (ENSO, IOD, and MJO) and seasonal flood variability in Bangladesh - Md Rashed Chowdhury; Adiba Mosharraf; Md. Ashraful Islam; Shamoeta Zaman; Md. Abdulla Hel Kafi; Md. Sohel Masud; SM Mahbubur Rahman (Theoretical and Applied Climatology, 2026)

Otolith weight as a predictor of age in Sillaginopsis panijus (Hamilton, 1822): Development of a preliminary age estimation model - Mohammad Rashed; KM Jakaria Shuvo; Siam Sheikh Sadi; Md Abdul Baten (Estuarine, Coastal and Shelf Science, 2026)

Habitat suitability analysis for sea cucumber mariculture development in the coastal waters of Bangladesh - Muhammad Mizanur Rahman; Subrata Sarker; Md. Rashed Talukder; Md. Shahadat Hossain; Md. Al Mamun; Tanjida Sultana (International Journal of Remote Sensing, 2026)

ENSO and seasonal climate variability in the Maldives: an analysis of early warning opportunities - Md Rashed Chowdhury; Azeema Ahmed; Sheena Moosa; Shazla Mohamed (Theoretical and Applied Climatology, 2025)

Nutrient Analysis of Raw and Sensory Evaluation of Cooked Red Tilapia Fillets (Oreochromis sp.): A Comparison Between Aquaculture (Red Kenyir™) and Wild Conditions - Aswir Abd Rashed; Nurliayana Ibrahim; Nurul Izzah Ahmad; Mariam Marip; Mohd Fairulnizal Md Noh; Mohammad Adi Mohammad Fadzil (Fishes, 2025)
The tilapia sector is advancing due to breakthroughs in aquaculture techniques and genetic enhancements. Comprehending sensory qualities is crucial for producers striving to meet market demands efficiently. As consumer preferences play a significant role in shaping the market, enhancing the sensory attributes of both farmed and wild red tilapia will be key to ensuring their success in the competitive aquaculture industry. One of Malaysia’s most prominent aquaculture projects is the Como River Aquaculture Project located in Kenyir Lake, where tilapia fish farming, trademarked as Red Kenyir™, is conducted. Thus, this study aimed to evaluate the nutrient analysis of raw and five sensory attributes (appearance, texture, smell, taste, overall quality) of filets from Red Kenyir™ and wild red tilapia (Oreochromis sp.). Red Kenyir™ were fed three different commercial diets (A, B, and C) from fingerling to adulthood, while wild tilapia (W) was sourced from the market. Proximate and nutritional analyses were conducted based on the standard food analysis protocol by AOAC/AOCS. To the best of our knowledge, this is the first study to comprehensively document the nutrient analysis of raw and consumer sensory perception of cooked Red Kenyir™ aquaculture tilapia in direct comparison with wild red tilapia. The sensory evaluation was conducted using a consumer preference test. Statistical analysis was performed using SPSS. Nutrient analysis showed that Red Kenyir™ tilapia had lower fat (0.25–1.37 g/100 g vs. 4.30 g/100 g) and lower energy (77.38–113.46 kcal/100 g vs. 132.79 kcal/100 g) levels. Protein levels varied across groups (19–26.54 g/100 g vs. 22.95 g/100 g). The tryptophan content of the Red Kenyir™ tilapia samples ranged between 0.13 and 0.23 g/100 g, while the wild tilapia contained 0.19 mg/100 g. Sensory evaluation with 36 panelists revealed no significant differences in appearance, texture, or smell (p > 0.05). However, wild tilapia scored slightly higher in taste (4.14) than Red Kenyir™ (3.54–3.71) for steamed preparation (p

Life cycle assessment of scaled-up pyrite-based solid-state batteries for energy storage applications - Md Rashed Hossain; Muyue Han; Lin Li (Journal of Cleaner Production, 2025)

Discovering the inherent properties of CdS/TiTe2/Cu2Te near infrared photodetector: A computational analysis - Md. Rashed Miah; Md. Islahur Rahman Ebon; Ahnaf Tahmid Abir; Jaker Hossain (Next Research, 2025)

Environmental sustainability practices in SMEs: Insights from integrated PLS-SEM and fsQCA approaches - Mohammad Imtiaz Hossain; Yasmin Jamadar; Mohammad Fakhrul Islam; Md. Rashed; Tania Akter (Journal of Cleaner Production, 2025)

Genome-wide analysis of TCP family genes and their constitutive expression pattern analysis in the melon (Cucumis melo) - Md Jahid Hasan Jone; Md Nure Adil Siddique; Manosh Kumar Biswas; Mohammad Rashed Hossain (Genes & Genomics, 2025)

A machine learning-based approach for flash flood susceptibility mapping considering rainfall extremes in the northeast region of Bangladesh - Md Enayet Chowdhury; A.K.M. Saiful Islam; Rashed Uz Zzaman; Sharfaraj Khadem (Advances in Space Research, 2025)

Capacity of detergent to increase the efficacy of bio-pesticides and chemical pesticides against giant mealybug, Drosicha mangiferae (Homoptera: Pseudococcidae) - Mohammad Shaef Ullah; Md. Mehedi Hassan Sharif; Ayon Dey; Md. Mojammel Haque; Md Tafsir Nur Nabi Rashed (International Journal of Tropical Insect Science, 2024)

Examining the synergy of green supply chain practices, circular economy, and economic growth in mitigating carbon emissions: Evidence from EU countries - A.K.M. Mohsin; Markus Gerschberger; Michael Plasch; Sayed Farrukh Ahmed; Arifur Rahman; Md. Rashed (Journal of Environmental Management, 2024)

Provenance signature and tectonic setting of the Pliocene Tipam Sandstone Formation from the Chittagong Tripura Fold Belt of the Bengal Basin - Abu Sadat Md. Sayem; Papiya Mondal; Md. Sha Alam; Rashed Abdullah; Julleh Jalalur Rahman; Rumana Yeasmin (Journal of Sedimentary Environments, 2024)

Sensitivity analysis of cumulus parameterization scheme and data sources to simulate thunderstorms over Bangladesh using WRF model - M. Mozammel Hoque; Md. Salah Uddin Afsar; Mohammad Rashed Iqbal Faruque; S. Jamal Ahmed; A.T.M. Kaosar Jamil; M.A.K. Mallik; S.M. Quamrul Hassan (Advances in Space Research, 2024)

Amplification of avian influenza virus circulation along poultry marketing chains in Bangladesh: A controlled field experiment - Lisa Kohnle; Tridip Das; Md. Helal Uddin; Sanjib Chandra Nath; Md. Abu Shoieb Mohsin; Rashed Mahmud; Paritosh Kumar Biswas; Md. Ahasanul Hoque; Dirk Udo Pfeiffer; Guillaume Fournié (Preventive Veterinary Medicine, 2024)

Optical Based Surface Plasmon Resonance Sensor for the Detection of the Various Kind of Cancerous Cell - Shah Ali Rafi; Wahiduzzaman Emon; Ahmed Afif Rafsan; Russel Reza Mahmud; Md. Faysal Nayan; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Development and Enhancement of PCF-based Sensors for Terahertz-frequency Region Breast Cancer Cell Detection - A. H. M. Iftekharul Ferdous; Laxmi Rani; Md. Safiul Islam; Khalid Sifulla Noor; Sourav Roy; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Innovative Refractive Index Sensor Utilizing Terahertz Spectrum for Early Cancer Detection: a Photonic Crystal Fiber Approach - A. H. M. Iftekharul Ferdous; Md Naimur Rahman Naim; Khalid Sifulla Noor; Diponkar Kundu; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Publisher Correction: Heat Stress Modulates Superoxide and Hydrogen Peroxide Dismutation and Starch Synthesis during Tuber Development in Potato - Jobadatun Naher; Zahid Hasan Sabuj; Sahida Islam Sumona; Sheba Pada Chakraborty; Mohammad Rashed Hossain; Md. Motiar Rohman; Ujjal Kumar Nath (American Journal of Potato Research, 2024)

Heat Stress Modulates Superoxide and Hydrogen Peroxide Dismutation and Starch Synthesis during Tuber Development in Potato - Jobadatun Naher; Zahid Hasan Sabuj; Sahida Islam Sumona; Sheba Pada Chakraborty; Mohammad Rashed Hossain; Md. Motiar Rohman; Ujjal Kumar Nath (American Journal of Potato Research, 2024)

GC-MS analysis and pharmacological potentiality of Lasia spinosa (L.) Thwaites leaves and fruit extracts: an in vitro and in silico studies - Md. Anamul Haq; Md. Eram Hosen; Rakhi Rani; Alomgir Hossain; Mahmudur Rahman; Md Sagor Ali; Rashed Zaman; Md. Khalekuzzaman; Md. Asadul Islam; Amti Kumar Dutta; Uzzal Kumar Acharjee (In Silico Pharmacology, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Linking green supply chain management practices and environmental performance in the manufacturing industry: a hybrid SEM-ANN approach - Rashed Al Karim; Mohammad Rokibul Kabir; Md Karim Rabiul; Sakia Kawser; Abdus Salam (Environmental Science and Pollution Research, 2024)

What drives carbon stocks in a mangrove forest? The role of stand structure, species diversity and functional traits - Md. Rashed Zaman; Md. Saidur Rahman; Shamim Ahmed; Pieter A. Zuidema (Estuarine, Coastal and Shelf Science, 2023)

Mapping of dressed and processed poultry products in Bangladesh: Identifying the food safety risks for policy intervention - Jinnat Ferdous; Md Helal Uddin; Rashed Mahmud; Mathew Hennessey; Abdullah Al Sattar; Suman Das Gupta; Justine S. Gibson; Robyn Alders; Joerg Henning; Guillaume Fournié; Md. Ahasanul Hoque (Veterinary Research Communications, 2023)
Bangladesh’s commercial poultry production is growing rapidly, including the commercial processing of poultry. This expansion of poultry processing plants is fueled by the belief that this sub-sector provides safer food and has less food-borne disease risks compared to traditional live bird markets (LBMs). The purpose of this study is to describe Bangladesh’s dressed and processed poultry production and distribution network (PDN), identify what and where quality control occurs, and suggest where improvements could be made. Engaging with PDN for dressed and processed poultry, we used in-depth interviews with key informants to identify the stakeholders involved and their connections with other poultry PDNs. In addition, we mapped out the supply and distribution of dressed and processed poultry and quality control processes occurring throughout the network. We argue that dressed and processed poultry PDNs are closely connected with traditional PDNs such as LBMs, with multiple crossover points between them. Also, there is a lack of consistency in quality control testing and a lack of meat traceability. Consequently, perceptions of dressed and processed poultry being safer than birds from LBMs needs to be treated with caution. Otherwise, unsubstantiated consumer confidence in dressed poultry may inadvertently increase the risk of food-borne diseases from these products.

Major and trace element geochemistry of the Atrai River sediments from the Bengal Basin (Bangladesh): implication for provenance, chemical weathering, and tectonic setting in the southeastern Himalaya - Abu Sadat Md. Sayem; Md. Rokonuzzaman; Md. Shams Shahriar; Rashed Abdullah; Zahidul Bari; Md. Sazzad Hossen (Arabian Journal of Geosciences, 2023)

Molecular docking and dynamics simulation approach of Camellia sinensis leaf extract derived compounds as potential cholinesterase inhibitors - Md. Eram Hosen; Md. Sojiur Rahman; Md Omar Faruqe; Md. Khalekuzzaman; Md. Asadul Islam; Uzzal Kumar Acharjee; Rashed Zaman (In Silico Pharmacology, 2023)

Abundance, characteristics, and spatial–temporal distribution of microplastics in sea salts along the Cox’s Bazar coastal area, Bangladesh - Muhammad Saiful Islam; Md. Rashed Hasan; Zahidul Islam (Environmental Science and Pollution Research, 2022)

Rainfall and sea-level variability in the face of changing El Niño: evidence from the U.S.-affiliated Pacific islands - Md. Rashed Chowdhury; Pao-Shin Chu; Ousmane Ndiaye; James T. Potemra (Meteorology and Atmospheric Physics, 2022)

Stock Assessment of Six Sciaenidae Species in the Bay of Bengal, Bangladesh Water Using a Length-Based Bayesian Biomass (LBB) Method - Rokeya Sultana; Qun Liu; Petra Schneider; Md. Abdullah Al-Mamun; Al Mamun; Md. Farhan Tazim; Mohammad Mojibul Hoque Mozumder; Mohammed Rashed Parvej; Md. Mostafa Shamsuzzaman (Fishes, 2022)
Six most abundant and commercially valuable croakers (Sciaenidae) stocks in the coastal water of Bangladesh were evaluated using a length-based Bayesian Biomass (LBB) approach. The ratios B/B0 (current relative biomass) were smaller than the BMSY/B0 in five of the six stocks. For the six estimated populations, two (Otolithes ruber and Pterotolithus maculatus) are grossly overfished, one (Otolithoides pama) is overfished, two (Johnius belangerii and Panna heterolepis) are slightly overfished, and only donkey croaker (Pennahia anea) is in the healthy (B/B0 > BMSY/B0) status. Furthermore, the optimal length at first capture (Lc_opt) was higher than the length at first capture (Lc) in four populations, indicating growth overfishing, suggesting that increasing mesh size would benefit the catch and biomass. Findings from the present study confirm the declining trend of fisheries resources, particularly the croaker species in the BoB, Bangladesh coastal water. Management strategies (such as effort control, choosing the appropriate mesh size, total allowable catch limit, identify and enhance protection of the feeding, breeding, and nursery ground, etc.) should be taken for the sustainable management and recovery of the country’s marine fishing resources, particularly the valuable croaker species.

Climate change vulnerability in Bangladesh based on trend analysis of some extreme temperature indices - Istiak Ahmed; Sheikh Ishtiaque; Taslima Zahan; Md. Saif Uddin Rashed; Ranjit Sen; Md. Faruque Hossain; Shyamal Brahma; Imrul Mosaddek Ahmed; M. Akhtar Hossain; Mohammad Akkas Ali; Abu Hena Sorwar Jahan; Sheikh Imtiaz; et al. (Theoretical and Applied Climatology, 2022)

Ag nanoparticle-decorated chitosan/SrSnO3 nanocomposite for ultrafast elimination of antibiotic linezolid and methylene blue - M. Faisal; Md Abu Rashed; Jahir Ahmed; Mabkhoot Alsaiari; Mohammed Jalalah; Saeed A. Alsareii; Farid A. Harraz (Environmental Science and Pollution Research, 2022)

Green building aspects in Bangladesh: A study based on experts opinion regarding climate change - Md. Arif Chowdhury; Hasnat Sabrina; Rashed Uz Zzaman; Syed Labib Ul Islam (Environment, Development and Sustainability, 2022)

Spatial variability of climatic hazards in Bangladesh - Md. Arif Chowdhury; Rashed Uz Zzaman; Nusrat Jahan Tarin; Mohammad Jobayer Hossain (Natural Hazards, 2022)

A Machine Learning-based Approach for Groundwater Mapping - Rashed Uz Zzaman; Sara Nowreen; Irtesam Mahmud Khan; Md. Rajibul Islam; Nabil Ibtehaz; M. Saifur Rahman; Anwar Zahid; Dilruba Farzana; Afroza Sharmin; M. Sohel Rahman (Natural Resources Research, 2022)

Application of remote sensing for salinity based coastal land use zoning in Bangladesh - Md. Manjur Morshed; Showmitra Kumar Sarkar; Md. Rashed Uz Zzaman; Md. Mazharul Islam (Spatial Information Research, 2021)

Plio-Pleistocene to Recent tectonostratigraphic evolution of the Lalmai anticline in the western Indo-Burman Range (Bangladesh): insights from lithofacies analysis and structural synthesis - Rashed Abdullah; Abu Sadat Md Sayem; Rumana Yeasmin; Mohammad Mashiur Rahman; Zahidul Bari; Farida Khanam (Arabian Journal of Geosciences, 2021)

Development of potential map for groundwater abstraction in the northwest region of Bangladesh using RS-GIS-based weighted overlay analysis and water-table-fluctuation technique - Sara Nowreen; Imran Hossain Newton; Rashed Uz Zzaman; A. K. M. Saiful Islam; G. M. Tarekul Islam; Md. Saiful Alam (Environmental Monitoring and Assessment, 2021)

TP53 genetic polymorphisms and susceptibility to cervical cancer in Bangladeshi women: a case–control study - Mohd Nazmul Hasan Apu; A. Z. M. Rashed; Tafsir Bashar; Md Morshadur Rahman; Md Shaki Mostaid (Molecular Biology Reports, 2020)

Molecular characterization of Acidovorax citrulli strain NIHHS15-280 causing bacterial fruit blotch disease in Korea and screening of resistance sources in melon - Md. Rafiqul Islam; Mohammad Rashed Hossain; Hoy-Taek Kim; Ujjal Kumar Nath; Md. Abuyusuf; Hee-Jeong Jung; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Epidemiological assessment of clinical poultry cases through the government veterinary hospital-based passive surveillance system in Bangladesh: a case study - Md. Ashiqur Rahman; Md. Mahbubur Rahman; Md. Sadeque Abdullah; Md. Abu Sayeed; Md. Harun Rashid; Rashed Mahmud; Joseph P. Belgrad; Md. Ahasanul Hoque (Tropical Animal Health and Production, 2019)

Climate change and variability impacts on the forests of Bangladesh – a diagnostic discussion based on CMIP5 GCMs and ENSO - Md. Rashed Chowdhury; Ousmane Ndiaye (International Journal of Climatology, 2017)
The aim of this study is to assess the evolution of forests in Bangladesh from the perspective of changing climate, with particular emphasis on the Sundarbans, the world's largest mangrove forest. Projections for temperature and rainfall change have been made using the latest Intergovernmental Panel on Climate Change‐Fifth Assessment Report ( IPCC‐AR5 ) general circulation models ( GCMs ) protocol (Coupled Model Intercomparison Project Phase 5, CMIP5 ) with 38 various GCMs and up to 105 model runs. The GCMs findings were verified by the published results of 11 regional climate models ( RCMs ) in the Coordinated Regional Climate Downscaling Experiment ( CORDEX )‐South Asia models with finer spatial resolution. A CMIP5 model‐based synthesis review on the future variability of El Niño‐Southern Oscillation ( ENSO ) has also been made, as both the seasonal temperature and rainfall variability in Bangladesh are correlated to ENSO . Both global and regional climate change scenarios indicate that temperature would continue to rise and total annual rainfall is likely to increase in the future. However, weak increases in rainfall combined with high increases in temperature would create a high demand and competition for water because of the higher evapotranspiration environment. In addition to changing climate, the interannual variability of ENSO would further aggravate problems because it displays important correlations with the variability of rainfall, temperatures, sea‐level, lightning, and forest fires in Bangladesh. This study strongly recommends that future climate change projections should be combined with interannual variability ENSO to improve climate perspectives for stronger forest capacity building efforts in Bangladesh.

First Record of Porpita porpita (Cnidaria: Hydrozoa) from the coral reef ecosystem, Bangladesh - M. Shah Nawaz Chowdhury; S. M. Sharifuzzaman; Sayedur Rahman Chowdhury; Md. Rashed-Un-Nabi; M. Shahadat Hossain (Ocean Science Journal, 2016)

An improved sea level forecasting scheme for hazards management in the US ‐affiliated Pacific Islands - Md. Rashed Chowdhury; Pao‐Shin Chu; Charles Chip Guard (International Journal of Climatology, 2014)
This study describes an improved seasonal sea level forecasting scheme by the Pacific ENSO Applications Climate Center ( PEAC ). Since 2005, an operational sea level forecasting scheme (3–5 months in advance) for the US‐affiliated Pacific Islands ( USAPI ) has been instrumental ( http://www.prh.noaa.gov/peac/sea‐level.php ). The El Niño‐Southern Oscillation ( ENSO ) climate cycle and the sea‐surface temperatures ( SSTs ) in the tropical Pacific Ocean are taken as the primary factors in modulating these forecasts on seasonal time scales. The current SST ‐based canonical correlations analysis ( CCA ) hindcast forecasts have been found to be skillful. However, the skill gradually decreases as the lead‐time increases. This has motivated us to revisit the forecasting scheme at PEAC . In contrast to previous endeavours which relied only on SSTs , we now incorporate both trade winds and SSTs for modulating sea level variability on seasonal time scales. The average forecasts for zero to three seasons' lead‐times are found to be 0.647, 0.598, and 0.625 for combined SST and the zonal component of the trade wind (U), SST , and wind (U), respectively. It is therefore revealed that the combined SST‐wind‐based forecasts are more skillful than the SST or wind‐based forecasts alone. It is particularly more efficient on longer time scales for most of the stations (e.g. 10–25% improvement on two to three seasons' lead‐times). The improvements of these forecasts have enabled the capability of our clients in the USAPI region to develop a more efficient long‐term response plan for hazard management.

Temporal and spatial distribution of fish and shrimp assemblage in the Bakkhali river estuary of Bangladesh in relation to some water quality parameters - Md. Rashed-Un-Nabi; Md. Abdulla Al-Mamun; Md. Hadayet Ullah; M. Golam Mustafa (Marine Biology Research, 2011)

Sea level extremes in the U.S.-Affiliated Pacific Islands—a coastal hazard scenario to aid in decision analyses - Md. Rashed Chowdhury; Pao-Shin Chu; Xin Zhao; Thomas A. Schroeder; John J. Marra (Journal of Coastal Conservation, 2010)

Variability and predictability of sea-level extremes in the Hawaiian and U.S.-Trust Islands—a knowledge base for coastal hazards management - Md. Rashed Chowdhury; P.-S. Chu; Thomas A. Schroeder; Xin Zhao (Journal of Coastal Conservation, 2008)

Seasonal sea‐level forecasts by canonical correlation analysis—an operational scheme for the U.S.‐affiliated Pacific Islands - MD. Rashed Chowdhury; Pao‐Shin Chu; Thomas Schroeder; Nicole Colasacco (International Journal of Climatology, 2007)
The objective of this study is to develop an operational canonical correlation analysis (CCA) statistical model for sea‐level forecasts in the U. S.‐affiliated Pacific Islands (USAPI) with lead times of several months or longer. The El Niño‐Southern Oscillation (ENSO) climate cycle and the sea‐surface temperatures (SSTs) in the tropical Pacific Ocean are taken as the primary factors in modulating sea‐level variability on the seasonal time scales. Observations revealed that the sea‐level variations in the USAPI are sensitive to ENSO cycle with low sea level during El Niño and high sea level during La Niña events. The correlation between the sea‐level variability and the fluctuations of tropical Pacific SSTs has been found to be strong. The cross‐validated results indicated that the SST‐based CCA model is potentially useful in predicting seasonal sea‐level variations in the USAPI. For all target seasons at 1‐ and 2‐season lead times, the average correlation skill has been found to be 0.50 or better. Based on this operational CCA model, the real‐time forecasts for seasonal sea‐level variations (i.e. deviations with respect to climatology) are published at the official web site of Pacific ENSO Applications Center (PEAC) ( http://lumahai.soest.hawaii.edu/Enso/peu/update.html ) for planning and decision options regarding hazard management in the USAPI. Copyright © 2007 Royal Meteorological Society

Consensus Seasonal Flood Forecasts and Warning Response System (FFWRS): An Alternate for Nonstructural Flood Management in Bangladesh - MD. Rashed Chowdhury (Environmental Management, 2005)

Hydro‐meteorological variability in the greater Ganges–Brahmaputra–Meghna basins - MD. Rashed Chowdhury; Neil Ward (International Journal of Climatology, 2004)
The flows of the Ganges, Brahmaputra and Meghna (GBM) are highly seasonal, and heavily influenced by monsoon rainfall. As a result, these rivers swell to their banks and often overflow during the monsoon months. This is most pronounced in the downstream regions, particularly in Bangladesh, which is the lowest riparian country. The objective of this paper is to study this hydro‐meteorological variability in the greater GBM regions, including the headwater regions in India and their role in streamflows in Bangladesh, and explore the large‐scale oceanic factors affecting this hydro‐meteorological variability. Global precipitation data, Bangladesh rainfall and streamflow records have been analysed and related to large‐scale climate patterns, including upstream rainfall, regional atmospheric circulation and patterns of sea‐surface temperature. The findings have quantified how the streamflows of these rivers in Bangladesh are highly correlated with the rainfall in the upper catchments with typically a lag of about 1 month. Therefore, streamflows in Bangladesh could be reasonably estimated for 1 to 3 months in advance (especially for the Ganges and Brahmaputra rivers) by employing simple correlation, if rainfall data from countries further up are available on a real‐time and continuous basis. In the absence of rainfall data, streamflow forecasts are still possible from unusually warm or cold sea‐surface temperatures in the tropics. The study concludes that hydro‐meteorological information flow between Bangladesh and other neighbouring countries is essential for developing a knowledge base for evaluating the potential implications of seasonal streamflow forecast in the GBM basins in Bangladesh. Copyright © 2004 Royal Meteorological Society

The Impact of `Greater Dhaka Flood Protection Project' (GDFPP) on Local Living Environment – The Attitude of the Floodplain Residents - Md. Rashed Chowdhury (Natural Hazards, 2003)

An Assessment of Flood Forecasting in Bangladesh: The Experience of the 1998 Flood - Md. Rashed Chowdhury (Natural Hazards, 2000)